Autologous chondrocyte implantation. Postoperative care and rehabilitation. Science and practice - Hambly, K.; Bobic, V.; Wondrasch, B.; van Assche, D.; Marlovits, S. (The American Journal of Sports Medicine, 2006)
Autologous chondrocyte implantation is an advanced, cell-based orthobiological technology used for the treatment of chondral defects of the knee. It has been in clinical use since 1987 and has been performed on 12 000 patients internationally; but despite having been in clinical use for more than 15 years, the evidence base for rehabilitation after autologous chondrocyte implantation is notably deficient. The authors review current clinical practice and present an overview of the principles behind autologous chondrocyte implantation rehabilitation practices. They examine the main rehabilitation components and discuss their practical applications within the overall treatment program, with the aim of facilitating the formulation of appropriate, individualized patient rehabilitation protocols for autologous chondrocyte implantation.